¿Son las universidades socialmente responsables? - Valle, Maria Belén Arias; Berbegal-Mirabent, Jasmina; Marimon-Viadiu, Frederic (education policy analysis archives, 2021)
The importance of university social responsibility (USR) is given by the commitment assumed by the university towards its stakeholders. This study aims at providing new insights on this topic, by analyzing the level of performance in USR that universities communicate. To this end, a structured procedure in five phases is proposed, analyzing elements of the strategic direction and considering the use of USR indicators which are grouped in the four main areas of impact (organizational, educational, cognitive and social). To do this, a qualitative approach has been followed, supported by the use of text analysis software as well as by frequency and spider diagrams. To illustrate its use and the type of analysis it allows, the procedure is applied to the case of the Catalan higher education system, presenting the results at different levels. The study ends with the discussion of the implications, a list of recommendations and suggestion for future works.
Keywords: Europe; Libre accès; Rôle des universités

¿Son las universidades socialmente responsables? - Valle, Maria Belén Arias; Berbegal-Mirabent, Jasmina; Marimon-Viadiu, Frederic (education policy analysis archives, 2021)
The importance of university social responsibility (USR) is given by the commitment assumed by the university towards its stakeholders. This study aims at providing new insights on this topic, by analyzing the level of performance in USR that universities communicate. To this end, a structured procedure in five phases is proposed, analyzing elements of the strategic direction and considering the use of USR indicators which are grouped in the four main areas of impact (organizational, educational, cognitive and social). To do this, a qualitative approach has been followed, supported by the use of text analysis software as well as by frequency and spider diagrams. To illustrate its use and the type of analysis it allows, the procedure is applied to the case of the Catalan higher education system, presenting the results at different levels. The study ends with the discussion of the implications, a list of recommendations and suggestion for future works.
Keywords: Europe; Libre accès; Rôle des universités